2016
DOI: 10.1152/ajpcell.00092.2016
|View full text |Cite
|
Sign up to set email alerts
|

Local coupling of TRPC6 to ANO1/TMEM16A channels in smooth muscle cells amplifies vasoconstriction in cerebral arteries

Abstract: [ANO1, also known as transmembrane protein 16A (TMEM16A)] is a Ca 2ϩ -activated Cl Ϫ channel expressed in arterial myocytes that regulates membrane potential and contractility. Signaling mechanisms that control ANO1 activity in arterial myocytes are poorly understood. In cerebral artery myocytes, ANO1 channels are activated by local Ca 2ϩ signals generated by plasma membrane nonselective cation channels, but the molecular identity of these proteins is unclear. Arterial myocytes express several different nonsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
0
35
1
1
Order By: Relevance
“…TMEM16A, also known as ANO1, DOG1, and ORAOV2, is a calcium-activated chloride channel (CaCC) (3)(4)(5) with physiological functions in epithelial tissues, exocrine glands, dorsal root ganglion neurons, and smooth muscles (6)(7)(8). TMEM16A has also been detected in multiple cancers, including breast cancer, head and neck squamous cell carcinomas (HNSCC), gastrointestinal squamous tumors (GIST), lung cancer, pancreatic cancer, and ovarian cancer (9,10).…”
mentioning
confidence: 99%
“…TMEM16A, also known as ANO1, DOG1, and ORAOV2, is a calcium-activated chloride channel (CaCC) (3)(4)(5) with physiological functions in epithelial tissues, exocrine glands, dorsal root ganglion neurons, and smooth muscles (6)(7)(8). TMEM16A has also been detected in multiple cancers, including breast cancer, head and neck squamous cell carcinomas (HNSCC), gastrointestinal squamous tumors (GIST), lung cancer, pancreatic cancer, and ovarian cancer (9,10).…”
mentioning
confidence: 99%
“…Channels can also associate with other cell surface molecules to form large macromolecular signaling complexes. Indeed, TMEM16A has been shown to interact with the ezrin-radixin-moesin network (Perez-Cornejo et al 2012) and with TrpV1 (Takayama et al 2015), TrpC6 (Wang et al 2016) and the IP3 receptor (Jin et al 2013) for coupled GPCR and ion channel signaling. Interestingly, the key signaling molecule -catenin involved in numerous cancers was also found recently to associate with the ion channels KCNQ1 (Rapetti-Mauss et al 2017) and BKCa (Bian et al 2011) to modulate Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM16A downregulation in tail arteries was found to be associated with reduction in CACNA1C protein (vascular L ‐type Ca 2+ channel) expression, TMEM16A modulates arterial contractility may be indirectly via regulation of CACNA1C expression (Jensen et al, ). Similarly, Q. Wang et al () found that canonical transient receptor potential receptor (TRPC6) channels stimulate TMEM16A currents via local Ca 2+ signaling. TMEM16A and TRPC6 channels are coupled in arterial myocytes and this interaction stimulates vasoconstriction in cerebral arteries (Q. Wang et al, ).…”
Section: Tmem16a and Hypertensionmentioning
confidence: 93%
“…Similarly, Q. Wang et al (2016) found that canonical transient receptor potential receptor (TRPC6) channels stimulate TMEM16A currents via local Ca 2+ signaling. TMEM16A and TRPC6 channels are coupled in arterial myocytes and this interaction stimulates vasoconstriction in cerebral arteries (Q.…”
Section: Tmem16a and Hypertensionmentioning
confidence: 97%
See 1 more Smart Citation